Plasma Free Thiol Levels during Early Sepsis Predict Future Renal Function Decline - Elisabeth C. van der Slikke; Lisanne Boekhoud; Arno R. Bourgonje; Tycho J. Olgers; Jan C. ter Maaten; Robert H. Henning; Harry van Goor; Hjalmar R. Bouma (MDPI AG, 2022)
Sepsis is a life-threatening syndrome characterized by acute organ dysfunction due to infection. In particular, acute kidney injury (AKI) is common among patients with sepsis and is associated with increased mortality and morbidity. Oxidative stress is an important contributor to the pathogenesis of sepsis-related AKI. Plasma free thiols (R-SH) reflect systemic oxidative stress since they are readily oxidized by reactive species and thereby serve as antioxidants. Here, we aimed to assess the concentrations of serum free thiols in sepsis and associate these with major adverse kidney events (MAKE). Adult non-trauma patients who presented at the emergency department (ED) with a suspected infection were included. Free thiol levels and ischemia-modified albumin (IMA), a marker of oxidative stress, were measured in plasma at baseline, at the ward, and at three months, and one year after hospitalization. Plasma free thiol levels were lower at the ED visit and at the ward as compared to three months and one year after hospital admission (p < 0.01). On the contrary, plasma levels of IMA were higher at the ED and at the ward compared to three months and one year after hospital admission (p < 0.01). Furthermore, univariate logistic regression analyses showed that plasma free thiol levels at the ED were inversely associated with long-term renal function decline and survival at 90 days (MAKE90) and 365 days (MAKE365) (OR 0.43 per standard deviation [SD] [0.22-0.82, 95% CI], p = 0.011 and OR 0.58 per SD [0.34-0.96, 95% CI], p = 0.035, respectively). A multivariate regression analysis revealed an independent association of plasma free thiols at the ED (OR 0.52 per SD [0.29-0.93, 95% CI], p = 0.028) with MAKE365, even after adjustments for age, eGFR at the ED, SOFA score, and cardiovascular disease. These data indicate the clear role of oxidative stress in the pathogenesis of sepsis-AKI, as reflected in the lower plasma free thiol levels and increased levels of IMA.